1977
DOI: 10.1063/1.323913
|View full text |Cite
|
Sign up to set email alerts
|

Stresses in superconducting solenoids

Abstract: This paper develops and summarizes analytical techniques for calculating radially dependent stress and strain in superconducting windings having anisotropic mechanical and thermal properties. The analysis considers stresses due to fabrication procedures, cooldown to helium temperature, and magnetic forces. Representative calculations for a particular superconducting coil are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 6 publications
0
32
0
Order By: Relevance
“…A second important finding concerned a coil that was trained / strained to 0.7 % hoop strain. Arp [12], as outlined earlier, showed that fibreglass between layers would be beneficial in reducing conductor hoop stress. Training did not re-occur until the hoop strain was very close to 0.7 %.…”
Section: Resin Cracking Wax and Frictionmentioning
confidence: 81%
“…A second important finding concerned a coil that was trained / strained to 0.7 % hoop strain. Arp [12], as outlined earlier, showed that fibreglass between layers would be beneficial in reducing conductor hoop stress. Training did not re-occur until the hoop strain was very close to 0.7 %.…”
Section: Resin Cracking Wax and Frictionmentioning
confidence: 81%
“…Numerical homogenization of the wire improves the estimation by introducing an orthotropic estimation in the linear elastic range of material behavior [47]. After the numerical homogenization of the wire, the winding, cool-down, and electromagnetic charging stress are then calculated and compared to the analytical methods described by Arp [50] and Caldwell [51]. …”
Section: Mechanical Support and Stress In Coil Bundlesmentioning
confidence: 99%
“…Plane strain approximation [9], [10] is used to analyze the stresses caused by cooldown from room temperature to cryogenic temperature, which is thought to be uniform. That is, the axial elastic strain is zero.…”
Section: B Stresses Caused By Cooldownmentioning
confidence: 99%